Educational theories in institutional socio educational projects: from enunciations to practices (Praxis Educativa, 2019)
This article accounts for an ongoing research, whose objective is the identification and analysis of different theories of education in the practices of democratic citizenship, at both state and privately-managed educational institutions of the Province of Córdoba. It is based on the analysis of the representations students, teachers, and administrators make of their practices. Based on previous researches within a line of research started in 2006, the study involves students, teachers, and administrators through the use of questionnaires, in-depth interviews, analysis of documents, and field observations. It inquires and organizes the pedagogical meanings these social agents within education grant to their practices of democratic citizenship. This article puts forward a classification of democratic practices, prepared as a temporary result of the interpretative analysis of the meanings explored in socio-educational projects, which the institutional actors identify as democratic spaces.
Keywords: educational theory; democracy; educational institutions; school participation.